Activated clotting time-guided heparinization during open AAA surgery: a pilot study - Liliane C. Roosendaal; Max Hoebink; Arno M. Wiersema; Jan D. Blankensteijn; Vincent Jongkind (Pilot and Feasibility Studies, 2024)
Abstract Background Arterial thrombo-embolic complications (TEC) are still common during and after non-cardiac arterial procedures (NCAP). While unfractionated heparin has been used during NCAP for more than 70 years to prevent TEC, there is no consensus regarding the optimal dosing strategy. The aim of this pilot study was to test the effectiveness and feasibility of an activated clotting time (ACT)-guided heparinization protocol during open abdominal aortic aneurysm (AAA) surgery, in anticipation of a randomized controlled trial (RCT) investigating if ACT-guided heparinization leads to better clinical outcomes compared to a single bolus of 5000 IU of heparin. Methods A prospective multicentre pilot study was performed. All patients undergoing elective open repair for an AAA (distal of the superior mesenteric artery) between March 2017 and January 2020 were included. Two heparin dosage protocols were compared: ACT-guided heparinization with an initial dose of 100 IU/kg versus a bolus of 5000 IU. The primary outcome was the effectiveness and feasibility of an ACT-guided heparinization protocol with an initial heparin dose of 100 IU/kg during open AAA surgery. Bleeding complications, TEC, and mortality were investigated for safety purposes. Results A total of 50 patients were included in the current study. Eighteen patients received a single dose of 5000 IU of heparin and 32 patients received 100 IU/kg of heparin with additional doses based on the ACT. All patients who received the 100 IU/kg dosing protocol reached the target ACT of > 200 s. In the 5000 IU group, TEC occurred in three patients (17%), versus three patients (9.4%) in the 100 IU/kg group. Bleeding complications were found in six patients (33%) in the 5000 IU group and in 9 patients (28%) in the 100 IU/kg group. No mortality occurred in either group. Conclusions This pilot study demonstrated that ACT-guided heparinization with an initial dose of 100 IU/kg appears to be feasible and leads to adequate anticoagulation levels. Further randomized studies seem feasible and warranted to determine whether ACT-guided heparinization results in better outcomes after open AAA repair.